HIV Risk Perception and Risky Behavior Among People Who Inject Drugs in Kermanshah, Western Iran - Noroozi, M.; Ahounbar, E.; Karimi, S.; Ahmadi, S.; Najafi, M.; Bazrafshan, A.; Shushtari, Z.; Farhadi, M.; Higgs, Peter; Rezaei, F.; Ghiasvand, H.; Sharhani, A.; et al. (Springer New York LLC, 2017)
Â© 2017, International Society of Behavioral Medicine. Purpose: Understanding and increasing awareness on individual risk for HIV infection as well as HIV risk perceptionâ€™s effects on different behavioral outcomes for people who inject drugs (PWID) is important for policymaking and planning purposes. The objectives of the present study were to determine whether HIV risk perception was associated with greater injection and sexual risk-taking behaviors among PWIDs. Method: We surveyed 460 PWID in Kermanshah regarding their demographic characteristics, sexual risk behaviors, HIV risk perception, and drug-related risk behaviors in the month prior to the study. Three classes of HIV risk perception were identified using ordinal regression to determine factors associated with HIV risk perception. Results: Study participants were categorized as follows: â€œlowâ€? (nÂ =Â 100, 22%), â€œmoderateâ€? (nÂ =Â 150, 32%), and â€œhighâ€? (nÂ =Â 210, 46%) risk perception for becoming infected with HIV. The odds of categorizing as â€œhighâ€? risk for HIV was significantly greater in PWID that reported unprotected sex (adjusted odds ratio (AOR) 2.4, p value 0.02), receptive syringe sharing (AOR 1.8, p value 0.01), and multiple sex partners (AOR 1.4, p value 0.03). PWID who reported unprotected sex had 2.7 times the odds of â€œhighâ€? risk perception when compared to PWID with â€œlowâ€? risk perception. Conclusion: Findings show that PWID could rate their HIV risk with acceptable accuracy. Additionally, perceived HIV risk was associated with many risk factors for transmission of HIV, emphasizing the importance of developing targeted prevention and harm reduction programs for all domains of risk behaviors, both sexual and drug-related use.